TEMPEH AGROINDUSTRY DEVELOPMENT STRATEGY IN GEUREUDONG PASE DISTRICT, NORTH ACEH REGENCY (CASE STUDY: TEMPEH AGROINDUSTRY MR. KAMTO) - Lira Fitria; Adhiana; Cut Rozana Sari; Muhammad Authar ND; Barmawi (LPPM Universitas Malikussaleh - Indonesia, 2026)
This research was carried out in Geureudong Pase District on June 28, 2025. This research aims to formulate the right development strategy for the tempe agroindustry in Geureudong Pase District, North Aceh Regency. The background of this research is that in Geureudong Pase District, Mr. Kamto has been running a tempeh business inherited by his parents for 23 years as a form of local food preservation. However, production is still limited to 20 kg of soybeans per day and has not been able to meet the increasing market demand. Therefore, strategic and innovative steps are needed to increase production and strengthen business competitiveness. The method carried out is a qualitative method with SWOT analysis. The results of the study show that the calculation of the SWOT matrix in Mr. Kamto's tempeh business, the intersection of the matrix X 1.40 and Y 1.25 shows that Mr. Kamto's tempeh business is in an aggressive position The results of alternative strategies that can be applied in the development of the tempe agro-industry are the SO strategy.